High-Velocity Impact Penetration Behavior of Recycled Aluminum Alloy 6061: A Brief Look - Latif, Irfan Alias Farhan; Mohd Nor, Mohd Khir (Journal of Advanced Mechanical Engineering Applications, 2023)
Aluminum demand is projected to increase in the future. To help meet the demand, recycling aluminum has been employed for quite some time. Conventional recycling of aluminum leads to CO2 and greenhouse gas emissions. Therefore, direct recycling techniques such as hot press forging are being used and researched to provide an alternate recycling route that leads to even lower emissions, material losses, and energy consumption. The recycled aluminum 6061 alloy obtained from hot press forging is relatively new. Hence, not much is known about its capabilities and properties, including its impact penetration behavior. In this study, recycled 6061 aluminum alloy plates of 5 mm obtained through hot press forging are used in high-velocity impact tests using a single-stage gas gun to test the material’s penetration behavior. Two tests are carried out at velocities ranging from 141 to 308 m/s, all resulting in full penetration. The material was observed to have decent energy absorption capabilities, ranging from 70% to 81%. The penetration behavior, however erratic, shows signs of both ductile and brittle failure modes.